Dynamics of hormonal and immunological parameters in patients with acute pleural empyema - V.V. Tkachenko; V.V. Boyko; V.V. Kritsak; A.L. Sochnieva; D.V. Minukhin; A.O. Merkulov; V.G. Hroma; V.V. Ponomarova; O.P. Sharmazanova (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. In case of acute pleural empyema, pronounced violations of cellular and humoral factors of immunity, as well as non-specific resistance of the body are revealed. The purpose of our research: to analyze and identify results of hormonal and immunological research in patients with acute pleural empyema depending on the severity of disease. Materials and methods. Dynamics of hormonal and immunological changes has been studied in 64 participants with acute pleural empyema who were treated with classical and minimally invasive surgical methods. Patients were classified into 5 groups depending on disease severity determined according to the criteria which included clinical and laboratory parameters, such as respiratory rate, heart rate, blood pressure, temperature reaction, the number of affected particles, leukocytosis, SpO2. All the patients underwent a standard examination, as well as determination of serum concentration of interleukin (IL) 6, IL-8, tumor necrosis factor (TNF) α, C-reactive protein (CRP). Results. Assessment of blood cytokines in patients with acute pleural empyema allows detecting hypercytokinemia with an increase in pro-inflammatory cytokines. Meanwhile, the degree of their elevation differed depending on the disease severity. Study of structure of cytokine status allowed us to identify that patients with severe course of pleural empyema had a significant increase in IL-6 and CRP. Nevertheless, the severe course of the disease is associated with insufficient increase of IL-8 and TNF-α. Patients of the older age group have deficiency of IL-8 and to a lesser extent IL-6. Complete blood count revealed higher total number of leukocytes, neutrophils, pronounced left shift, increased erythrocyte sedimentation rate in patients with a severe course of the disease. Conclusions. There have been identified factors which affect severe course of acute pleural empyema: a decrease in oxygen saturation to less than 94 %, severity of dyspnea which exceeds 2 points on the Borg scale, damage to 3 or more segments of lung tissue, and also numerous clinical signs of violation of anti-infective protection, pronounced decrease in neutrophils, an increase in the concentration of CRP and insufficient increase of IL-8 and TNF-α in blood serum.